Transit-oriented development and ports: A national analysis in the United States - John Renne (Journal of Transport and Land Use)
This study quantified the number of fixed-transit station areas, by transit-oriented development (TOD) typology, close to major sea and river port facilities across the United States. Moreover, the study analyzed population, job, transportation, and built environment characteristics near ports. The National TOD Database was combined with the National Transportation Atlas Database, and geographic information systems analysis was utilized to isolate all stations located within a half-mile, one mile, and three miles of major ports. Findings showed that TODs are located as close as a half-mile to some of the largest ports in the United States, including Boston, Chicago, Miami, and San Francisco/Oakland. Twenty-one percent of all stations were located within three miles of major ports across the nation; thus, TODs and major ports can successfully coincide despite tensions that may arise over congestion. Few studies have examined integrated land use and transportation planning for TODs near major ports. This study recommends ideas for future quantitative and qualitative research.